Managing Climate Change Risks in Africa - A Global Perspective - Adenle, Ademola A.; Ford, James D.; Morton, John; Twomlow, Stephen; Alverson, Keith; Cattaneo, Andrea; Cervigni, Rafaello; Kurukulasuriya, Pradeep; Huq, Saleemul; Helfgott, Ariella; Ebinger, Jane O. (Elsevier, 2018)
Africa is projected to experience diverse and severe impacts of climate change. The need to adapt is increasingly recognized, from the community level to regional and national governments to the donor community, yet adaptation faces many constraints, particularly in low income settings. This study documents and examines the challenges facing adaptation in Africa, drawing upon semi-structured interviews (n = 337) with stakeholders including high-level stakeholders, continent-wide and across scales: in national government and UN agencies, academia, donors, non-governmental organizations, farmers and extension officers. Four key concerns about adaptation emerge: i) Climate data, scenarios and impacts models are insufficient for supporting adaptation, particularly as they relate to food systems and rural livelihoods; ii) The adaptation response to-date has been limited, fragmented, divorced from national planning processes, and with limited engagement with local expertise; iii) Adaptation policies and programs are too narrowly focused on explicit responses to climate change rather than responses to climate variability or broader development issues; and iv) Adaptation finance is insufficient, and procedures for accessing it present challenges to governments capacities. As a response to these concerns, we propose the 4-Cs framework which places adaptation for Africa at the center of climate projections, climate education, climate governance and climate finance, with corresponding responsibilities for government and non-government actors.